Experimental Investigation of Pure Hydrogen Flame in a Matrix Micro-Mixing Combustor - Zhenzhen Feng; Xiaojing Tian; Liangliang Xu; Xi Xia; Fei Qi (Aerospace, 2025)
Pure hydrogen combustion is a critical pathway to achieving zero-carbon emissions for the gas turbine industry. Micro-mixing combustion is one of the most widely attractive hydrogen combustion methods in gas turbines. This study investigates pure hydrogen flame in a 3 × 3 matrix micro-mix combustor. The setup includes nine micro-mix injectors, each equipped with a bluff body and a hydrogen injection tube. The OH* chemiluminescence imaging and PIV (Particle Image Velocimetry) techniques were employed to visualize the single- and triple-flame morphology and flow field under various operating conditions. The results show that equivalence ratio, flow rate, and air injector exit angle can influence the flame structure and combustion characteristics, providing an insightful understanding of micro-mix pure hydrogen combustion.